Biofuel Energy in the Post-oil Era - Lisin, Anton (International Journal of Energy Economics and Policy, 2020)
The article proposes evaluating the costs of bioenergy supplies in Russia utilizing a method that is based on energy analysis. The main disincentivizing factor is not as much limited resources as the marginal cost of producing biofuels and the possibility of using cost-effective ways of reducing greenhouse gas emissions, including carbon capture and storage, alternative forms of renewable energy, energy efficiency and energy savings. In this situation, the possibility of progressive development of the global market for biofuels can only be achieved by fundamental changes in the industry, that are determined by the peculiarities of scientific progress. The author also identifies several technological, economic, financial and natural factors constraining large-scale advances in bioenergy. Comparing innovation policies of various countries of the world and paper notes of industrialized countries, we can see a high level of R&D investments in the field of biofuel technologies. Keywords: energy sources, biodiesel, fuel butanol, fuel ethanol. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8769